Genetic relationships between sex-specific traits in a crossbred beef cattle population - Speer, Nevil, C., author; Brinks, James S., advisor (Colorado State University. Libraries, 1993)
Data used were obtained from the Fort Keogh Livestock and Range Research Laboratory (LARRL), Miles City, Montana. Data were from a crossbreeding experiment involving Hereford, Angus and Charolais cattle collected from 1962 to 1977. Traits studied and considered separate with respect to sex, included male and female birth weight (BWM and BWF), weaning weight (WWM and WWF), and postweaning average daily gain (ADGM and ADGF). Other traits studied were average adjusted mature weight (MW) of cows and fat thickness (FT), ribeye area (REA), yield grade (YG), quality grade (QG) and days on feed (DOF) of bulls and steers slaughtered at a weight constant endpoint of 1000 - 1050 lb. Multi-trait sire-maternal grandsire REML analyses were performed on straightbred and crossbred Hereford, Angus, and Charolais cattle. Observations on 2888 animals contributed to development of the A-inverse which represented relationships among 138 sires and maternal grandsires. Models for BWM, BWF, WWM, WWF, ADGM, ADGF, and MW analyses models included birth year, age of dam (2, 3, 4, 5+) and linear regression on weaning age. The DOF analysis model included birth year, age of dam, sex of calf (bull vs steer), age of dam-sex of calf interaction and linear regression on weaning age. Carcass trait (FT, REA, YG, QG) models included birth year, age of dam, sex of calf, age of dam-sex of calf interaction and linear regression on carcass weight. Linear regressions on individual breed percentage, combined reciprocal cross percentage (individual heterosis), dam breed percentage and dam combined reciprocal cross percentage (maternal heterosis) were also included in all models for analyses of all traits of interest. Correlations between direct components of birth weight, weaning weight, and postweaning average daily gain considered separately between male and female calves were .93, .90 and .74 respectively. The correlation between direct components of MW and DOF was -.66. Correlations between direct components of MW and carcass traits were -.54, -.18, -.18, and .41 for FT, REA, YG and QG, respectively. Correlations between maternal components of birth weight, weaning weight, and postweaning average daily gain considered separately between male and female calves were .86, .98 and .42, respectively. The correlation between maternal components of MW and DOF was -.71. Correlations between maternal components of MW and carcass traits were .40, .10, .08, and -.06 for FT, REA, YG and QG, respectively. Correlations between mat-dir and dir-mat of the same traits studied were moderate and ranged from -.44 to .47. Predictions of correlated responses in mature weight per standard deviation of direct response in male carcass traits were -32 lb, -13 lb, -10 lb, and 31 lb respectively for FT, REA, YG and QG. Correlated response predictions indicate selection for improved carcass cutability on a weight constant basis (increased leanness and decreased yield grades) would increase mature weight while selection for increased ribeye area and decreased quality grade scores (favorable) on a weight constant basis would result in decreased mature weights of females. Strong selection pressure for leanness may be antagonistic to commercial beef producers since results suggest sires selected on the basis of reducing fat in steer progeny also produce females that are larger at maturity when cattle are slaughtered at a constant weight endpoint. It should be noted, however, relationships between carcass traits and mature weight may differ when cattle are slaughtered at a constant age endpoint.
Covers not scanned.
Keywords: Beef cattle -- Breeding; Beef cattle -- Genetics; Beef cattle